Pembinaan Kerohanian Mahasiswa Politehnik Negeri Medan Meningkatkan Jiwa Daya Saing - Hasahatan Hutahaean; Suherman Suherman; Linda Zenita Simanjuntak; Asmat Purba (Apik Cahaya Ilmu, 2026)
Higher education institutions (HEIs) are part of society, providing learning (scientific) and character development (e.g., temperament) for students entering the workforce. In the workplace, competitiveness, productivity, innovation, and religious character are some of the key determinants of success, combined with numerous factors. Spirituality plays a crucial role in shaping strong student character for the future. With strong spirituality, students have a solid foundation to become honest workers, resistant to temptation and sway. Training was provided to students at the Medan State Polytechnic, focusing on the study of Scripture, specifically on enhancing competitiveness. After the training, it was evident that their understanding of Scripture exploration was sound and applicable. A strong work ethic, persistence in competition, and a strong faith-based character were formed based on the messages of Scripture that were read and explored. This sound understanding of Scripture will continue to be developed through the methods of exploration that have been mastered. Gradually, students are formed and prepared to enter the workforce upon completion of their education